2007
DOI: 10.1016/j.neuron.2007.02.029
|View full text |Cite
|
Sign up to set email alerts
|

The Emergence of Contrast-Invariant Orientation Tuning in Simple Cells of Cat Visual Cortex

Abstract: Simple cells in primary visual cortex exhibit contrast-invariant orientation tuning, in seeming contradiction to feed-forward models that rely on lateral geniculate nucleus (LGN) input alone. Contrast invariance has therefore been thought to depend on the presence of intracortical lateral inhibition. In vivo intracellular recordings instead suggest that contrast invariance can be explained by three properties of the excitatory pathway. (1) Depolarizations evoked by orthogonal stimuli are determined by the amou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

44
342
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 231 publications
(392 citation statements)
references
References 59 publications
44
342
1
Order By: Relevance
“…For example, for the representative cell in Figure 5A, such tuning curves are shown in Figure 7A. One might expect that, if the membrane potential of a cell were far below spike firing threshold in the drifting grating experiment, the measured orientation selectivity would be greater than that of the predicted tuning curve because of the iceberg effect (Priebe and Ferster, 2006;Finn et al, 2007). Good agreement between predicted and measured orientation selectivity would suggest the opposite, that the membrane potential of the cell was not far below spike-firing threshold during the drifting grating experiments.…”
Section: R͑͒ ϭ E͑͒ ϫ U͑͒mentioning
confidence: 97%
See 2 more Smart Citations
“…For example, for the representative cell in Figure 5A, such tuning curves are shown in Figure 7A. One might expect that, if the membrane potential of a cell were far below spike firing threshold in the drifting grating experiment, the measured orientation selectivity would be greater than that of the predicted tuning curve because of the iceberg effect (Priebe and Ferster, 2006;Finn et al, 2007). Good agreement between predicted and measured orientation selectivity would suggest the opposite, that the membrane potential of the cell was not far below spike-firing threshold during the drifting grating experiments.…”
Section: R͑͒ ϭ E͑͒ ϫ U͑͒mentioning
confidence: 97%
“…Many experimental studies (Nelson and Frost, 1978;Sillito et al, 1980;Bonds, 1989;Volgushev et al, 1993;Sato et al, 1996;Ringach et al, 2002a,b;Shapley et al, 2003) concluded that suppressive or inhibitory cortical mechanisms were involved. However, more recent studies Freeman et al, 2002;Priebe and Ferster, 2006;Finn et al, 2007;Koelling et al, 2008) suggested that the suppressive effects studied earlier in experiments that used plaids and drifting gratings as stimuli might be due to nonlinearities in the retina and/or LGN. These reexaminations of the neuronal mechanism of orientation selectivity motivated us to make a quantitative assessment of the contribution of untuned suppression.…”
Section: Neuronal Processes Involved In Orientation Selectivitymentioning
confidence: 99%
See 1 more Smart Citation
“…Using this equation for our simulation yielded qualitatively similar results. The noise that comes with such balanced input has recently been shown to account for contrast normalization in the primary visual cortex of cats (Finn et al 2007). A second mechanism that could implement gain modulation is synchrony of inhibitory cells (Tiesinga et al 2004).…”
Section: Gain and Threshold Modulationmentioning
confidence: 99%
“…Experimentally, it was shown that cortical neurons' degree of orientation selectivity is independent of the stimulus contrast, and that this prompts the network to operate in a high-gain regime, as close to the transition to bistability as possible, but that no bistable behavior of simple or complex cells has been observed in the input layer of the primary visual cortex [3,5,46,47,107,110,111,119]. The constraints laid out by this fluctuation-controlled criticality scenario allows us to tune the large-scale model network so that it operates in the regime just below the critical transition point to bistability [100,101,130], whose existence and properties are well understood through our kinetic-theoretic coarse-graining approach.…”
Section: 6 and [130] For A Detailed Explanation) [Reproduced With Pmentioning
confidence: 99%